2021
DOI: 10.3390/nu13051556
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Chronic Pain Treatment with Enhanced Neuroplastic Responsiveness: A Pilot Randomized Controlled Trial

Abstract: Chronic pain affects mental and physical health and alters brain structure and function. Interventions that reduce chronic pain are also associated with changes in the brain. A number of non-invasive strategies can promote improved learning and memory and increase neuroplasticity in older adults. Intermittent fasting and glucose administration represent two such strategies with the potential to optimize the neurobiological environment to increase responsiveness to recognized pain treatments. The purpose of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Intermittent fasting is a popular approach to stimulate autophagy in the brain and thereby reduce the accumulation of pathological proteins [ 57 , 58 , 59 ]. Intermittent fasting has also been suggested to support the current pain treatments [ 60 ]. A continuous trehalose administration over an extended period may mimic long-term nutrient deficiency for neurons, and one may speculate that neurons will try to save energy and reduce their activity.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent fasting is a popular approach to stimulate autophagy in the brain and thereby reduce the accumulation of pathological proteins [ 57 , 58 , 59 ]. Intermittent fasting has also been suggested to support the current pain treatments [ 60 ]. A continuous trehalose administration over an extended period may mimic long-term nutrient deficiency for neurons, and one may speculate that neurons will try to save energy and reduce their activity.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to chronic pain, an IF pilot study was completed on middle and older adults with chronic knee pain. Based on three 16 h fasts over a ten-day period, study findings indicated that the regimen was feasible, acceptable, and without adverse events [174]. Given the consistent body of evidence regarding neuroplastic benefits, IF may also be effective as an adjuvant treatment [49,175].…”
Section: Non-invasive Pain Managementmentioning
confidence: 96%
“…Although the sample sizes were small and improvements in fecal flora were not indicated, patterns of clinical improvements were observed in both groups with significance for the individuals with rheumatoid arthritis only [190]. Additionally, a pilot study demonstrated the feasibility and acceptability of three times a week 16 h fast in individuals with chronic musculoskeletal pain [174]. Further, limited fasting trials have been conducted in health conditions associated with chronic pain.…”
Section: Considerations and Contraindicationsmentioning
confidence: 98%
“…Neuroinflammation may represent a form of neuroplasticity that can theoretically be reversed by neuroplastic interventions. For example, accruing evidence suggests significant cross-correlation between the neuroimmune system and neuroplastic mechanisms in responsiveness to chronic pain [30,31], neuronal adaptation in mood disorders [32], neuroimmune plasticity factors involved in central nervous system injury such as traumatic brain injury, spinal cord injury, and/or stroke [14,33], and immune macroenvironment plasticity in cancer models [34], to name a few. Neuroinflammation manifested by prolonged cytokine signalling amplified through the central nervous system cytokine network, causes detrimental effects to neurotransmitter activity, synaptic plasticity, neuroendocrine function, and resultant behaviors/symptoms [31].…”
Section: Re-thinking Treatment Of Neuroinflammation Through the Lens ...mentioning
confidence: 99%